Interrogating global narratives of trans queerness. Well-being and agency? Or more stories of trans trauma? - Vicars, Mark; Milenkovic, James (Frontiers in Sociology, 2024)
In the contemporary ethnosphere an unprecedented swathe of anti-trans measures has been executed through the frenzied repealing of rights, freedoms, and bodily movements of trans people within key arenas of public life: legal, medical, sporting, educative, and public accommodations. Concurrently, essentialist and pathologizing rhetoric from politicians, commentators, authors, and journalists are daily utterances which resound and reverberate within and across public consciousness, leading to dis-information and the stoking of fears. Vectored through a trauma-informed lens, this conceptual paper emplots anti-trans and transphobic discourses within a psycho-social tapestry of collective cultural trauma